AKIBAT HUKUM TERHADAP PERJANJIAN JUAL BELI OBYEK JAMINAN FIDUSIA (MOBIL) YANG DILAKUKAN DI BAWAH TANGAN ANTARA DEBITUR DENGAN PIHAK KETIGA TANPA MELALUI LEMBAGA PEMBIAYAAN (STUDI PUTUSAN PENGADILAN NEGERI PEKANBARU NO.29/PDT-G/2014/PN-PBR) - Saraswati, Ivoni; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
At the current time, the purchase of goods can be made in cash or credit. Credit as an alternative way in which to meet the needs of the people is one example of financial services products. In UU No. 42 of 1999 on Fiduciary, to ensure the security of credit implementation process, the credit object can be registered into places Fiduciary. When the process of implementation of payment credits pengangsuran, can occur alienation process object Fiduciary conducted debtor to another party, or known as the credit over. Diversion are performed by the debtor to third parties are often not notified to the financing institutions. Diversion is done only through agreement under hand, which according to the rules can only be strong evidence when the parties do not recognize or deny his signature. When a third party take care of the administrative process Object Fiduciary, problems will arise when one party disappeared in the process of Fiduciary Object that without going through Financing Institution.Issues that will be examined are: First, What is the legal effect of the purchase agreement Fiduciary Object (car) conducted under the hands of the debtor with a third party without going through a financial institution? Second, whether the consideration of judges in giving judgment in Case 29 / PDT-G / 2014 / PN-PBR has been in accordance with the principle of legal certainty?This type of research is a normative legal research. Discussing about the legal analysis that is recorded in the book. The data used is literature study include among other official documents, books, research results so forth. Data was analyzed qualitatively in drawing conclusions using deductive thinking.Results from this study were first, Effects of the transfer object Fiduciary conducted under the hand without going through a financial institution is the agreement null and void because it conflicts with the law. Second, consideration of the judge in deciding Case No.29 / PDT-G / 2014 / PN-PBR does not meet the principle of legal certainty. Suggestions of authors First, the transfer of the object through the fiduciary must Financing Institutions and using authentic deed Second, the judges ruling should satisfy the principle of legal certainty, without neglecting the rules of law.Keywords: Financing Agency-Fiduciary Transfer of Object-Under Hand